Family violence and social change in the Pacific Islands
1 online resource.
Keywords: "The Pacific Islands have some of the highest rates of family violence in the world. Addressing the contemporary mutations of Pacific Island families and the shifting understandings of violence in the context of rapid social change, this book investigates the conflict dynamics generated by these transformations. The contributors draw from detailed case studies in a range of Pacific territories to examine family violence in relation to the social, economic and political situation of native populations as well as individual, collective and institutional responses to the development of violence within and upon the family. They focus on vernacular understandings, conflicting social norms, the emergence of different types of violent patterns, the impact of violence on individuals and communities, and local attempts at mitigating or combating it. Combining ethnographic expertise with engaged scholarship, this volume offers a vivid account of ongoing social change in Pacific Island societies and a crucial contribution to the understanding of family violence as a social process, cultural construct, and political issue. This book will appeal to scholars with interests in the sociology of violence and the family, Pacific studies, development studies, and the social and cultural anthropology of Oceania"--